A Case of Sporadic Creutzfeldt–Jacob Disease with Unusually Long Survival: Correlation with Clinical Features, Electroencephalogram, and Brain Magnetic Resonance Imaging - Chih-Hao Jason Lin (International Journal of Gerontology, 2012)
Dementia in the elderly is the most common neurodegenerative disease and places a huge burden on public health. Sporadic Creutzfeldt–Jacob disease (sCJD) is sometimes diagnosed in people with dementia; it develops in a rapid and progressive manner and has a short survival duration. The critical issue for sCJD is its transmissible nature. Besides rapid and progressive dementia, two out of four motor symptoms are assessed for a definitive diagnosis, including myoclonus, cerebellar problems, extrapyramidal/pyramidal features, and akinetic mutism. Here we report on a 77-year-old woman with initially pure dementia. Sequential neuroimaging revealed progressive isolated cortical effects over a period of 3 years. Basal ganglia involvement on neuroimaging and generalized periodic sharp wave complexes on electroencephalogram were delayed until the onset of reflex myoclonic jerks occurred 3 years after the onset of dementia. The patient survives, with an unusually long duration for sCJD. According to the clinical and laboratory features observed in this case, awareness of pure dementia with delayed onset of characteristic electroencephalogram features and isolated cortical effects on neuroimaging may predict unusually long survival in sCJD.